2008
DOI: 10.1007/bf03175580
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation parameter and partial biochemical characterisation of milk clotting enzyme from Chinese distiller’s yeast

Abstract: A strain F34 producing milk clotting enzyme with high yield was obtained from Chinese distiller's yeast, using casein plate prescreening and fermentation reselection. The optimum fermentation medium for milk clotting enzyme production was as follows: 5.0% rice flour and bran digest, 5.0% bean flour digest, 0.5% CaCl 2 , 0.5% KCl, initial pH 4.5. The optimal fermentation parameters was at 34 °C for 60 h. The enzyme action was optimal at 50 °C and at about pH 5.5. In the absence of substrate the enzyme showed go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…Fermented milk products are becoming increasingly popular because of the numerous health benefits associated with highly digestible nutrients especially for individuals with lactose maldigestion, high biochemical (Wu et al 2008) and antioxidant activities (Kullisaar et al 2003) and probiotic organism colonisation of intestine after ingestion (Korcznska et al 2008). The addition of some materials, particularly fruits, into yogurt is practiced to increase the appealing taste of yogurt (Clark and Plotka 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Fermented milk products are becoming increasingly popular because of the numerous health benefits associated with highly digestible nutrients especially for individuals with lactose maldigestion, high biochemical (Wu et al 2008) and antioxidant activities (Kullisaar et al 2003) and probiotic organism colonisation of intestine after ingestion (Korcznska et al 2008). The addition of some materials, particularly fruits, into yogurt is practiced to increase the appealing taste of yogurt (Clark and Plotka 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is helpful in practice when the maximum milk-clotting activity occurs at the original pH of the medium. The production of milk-clotting enzyme by Bacillus licheniformis (D'Souza and Pereira 1982) and Amylomyces rouxii (Yu and Chou 2005) was highest in medium with an initial pH of 7, while maximum milk-clotting enzyme production by B. subtilis Natto (Shieh et al 2009) and strain F34 (Wu et al 2008) was reported with initial culture pH of 6.0 and 4.5, respectively. The results of this study and earlier reports suggest that the optimal initial pH of the medium for production of the milk-clotting enzyme varies depending on the culture medium and the test organism.…”
Section: Resultsmentioning
confidence: 94%
“…Immobilized lactase from A. oryzae is particularly suited for continuous lactose hydrolysis in acid whey. Also here, immobilization improved continuous lactose hydrolysis [7]. Accordingly, Mariotti et al [69] indicated that the stability and the hydrolysis activity of whey lactose by a silica-immobilized beta-galactosidase from A. oryzae within a continuous reactor process increased compared to non-immobilized systems.…”
Section: Advantages and Disadvantages Of Immobilized Enzymesmentioning
confidence: 92%
“…The milkclotting rate correlates to the enzymatic proteolytic activity associated with reduced thermal stability. Wu et al [7] studied a milk-clotting enzyme from Chinese distiller's yeast and observed strong milk-clotting activity and weak unspecific proteolytic activity. Interestingly, the enzymological characteristics of this microbial enzyme were similar to calf rennet.…”
Section: Milk Clotting With Proteasesmentioning
confidence: 98%
See 1 more Smart Citation